Contracting and Providing Basic Health Care Services in Honduras : A Comparison of Traditional and Alternative Service Delivery Models - Garcia Prado, Ariadna; Lao Peña, Christine (World Bank, Washington, DC, 2013)
This study uses data from health facility and patient exit surveys carried out in 2006 in Honduras to examine the characteristics of two basic health care provision models: a traditional Ministry of Health (MOH) public health care one versus a community based one also known as 'alternative' or 'public-social'. The author compare these models based on access, quality, costs, productivity, and management autonomy. While the alternative model has higher unit costs for drugs, it also has higher labor productivity. The fact that alternative providers are held accountable through performance-based contracts and that their personnel are hired on a contractual basis and can be demoted or even fired may account for their stronger performance relative to traditional providers whose personnel are centrally hired civil service staff. The findings support the alternative model as a viable option to expand services to other areas of Honduras that lack health services, compensating for the MOH's insufficient capacity to deliver and manage health care services in poor and remote areas. Some elements of this model such as performance-based agreements and other incentives can be also incorporated in the management and implementation of the traditional MOH health units in order to improve their performance. As the alternative models increase in number, it will be important to continue to evaluate their performance and to also analyze whether facility performance differs based on type of management (for example, whether the facility is managed by a municipality or an association of municipalities, a non-government organization, or community based organization).